Premio "ECOSISTEMAS" al mejor resumen de tesis publicado en esta revista. - Navarro, L. (Ecosistemas, 2010)
Navarro, L. (2009). Premio "ECOSISTEMAS" al mejor resumen de tesis publicado en esta revista. Ecosistemas 18(3):26.